The Internet of Things - Floerkemeier, Christian (Springer, 2017)
ThisvolumecontainstheproceedingsoftheInternetofThings(IOT)Conference 2008, the ?rst international conference of its kind. The conference took place in Zurich,Switzerland, March26–28,2008. The term ‘Internet of Things’ hascome to describe a number of technologies and researchdisciplines that enable the - ternet to reach out into the real world of physical objects. Technologies such as RFID, short-range wireless communications, real-time localization, and sensor networks are becoming increasingly common, bringing the ‘Internet of Things’ into industrial, commercial, and domestic use. IOT 2008 brought together le- ing researchersand practitioners, from both academia and industry, to facilitate the sharing of ideas, applications, and research results. IOT 2008 attracted 92 high-quality submissions, from which the technical program committee accepted 23 papers, resulting in a competitive 25% acc- tance rate. In total, there were over 250 individual authors from 23 countries, representing both academic and industrial organizations. Papers were selected solely on the quality of their blind peer reviews. We were fortunate to draw on the combined experience of our 59 program committee members, coming from the most prestigious universities and research labs in Europe, North America, Asia, and Australia. Program committee members were aided by no less than 63 external reviewers in this rigorous process, in which each committee member wrote about 6 reviews. The total of 336 entered reviews resulted in an average of 3. 7 reviews per paper, or slightly more than 1000 words of feedback for each paper submitted.